Juvenile Works about our Being by Lithuanian Thinkers of the 20th-21st century - Tijūnėlienė, Ona (Acta Paedagogica Vilnensia, 2005)
The research is aimed at revealing the interpretations of the essence of human being and existence in juvenile works of Lithuanian thinkers (20th-21st century). The results of the research show that in the latter years' literature it is written both about objective and subjective being. Being is cognitive and sciences of gnosticology and psychology help to cognize it. The reality is cognized by senses and logical thinking. A word and speech play an important role in cognition. Beside that, a word helps to cognizc oneself. The authors are writing about an intuitive cognition of reality. The end of individual’s being on earth is determined by decay of organism due to different reasons. Fight between life and death that is eternal is won by life. Spirit is accepted as immortal in this book. In the discussed publications the youth gets understandable and consistent explanation about the essence of being and the significance of existence.
Keywords: being; human existence; the universe; the Earth; death; cognitive methods; spirit; spirituality